Semantically Enriched Data Access Policies in eHealth. - Drozdowicz, Michał; Ganzha, Maria; Paprzycki, Marcin (Journal of Medical Systems, 2016)
Internet of Things (IoT) requires novel solutions to facilitate autonomous, though controlled, resource access. Access policies have to facilitate interactions between heterogeneous entities (devices and humans). Here, we focus our attention on access control in eHealth. We propose an approach based on enriching policies, based on well-known and widely-used eXtensible Access Control Markup Language, with semantics. In the paper we describe an implementation of a Policy Information Point integrated with the HL7 Security and Privacy Ontology.